Integration of Pesantren and Islamic School Curricula: Enhancing Qur’an Memorization Quality - Ahmad Yukha Dalhari; Emi Lilawati (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study investigates the management and impact of curriculum integration between pesantren and Islamic schools, focusing on its influence on students’ Qur’an memorization quality and the challenges encountered in implementation. Employing a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation involving school principals, curriculum coordinators, pesantren leaders, ustadz tahfidz, and nine student participants. Data analysis followed the Miles and Huberman model, encompassing data reduction, presentation, and conclusion drawing, with validity ensured through source and method triangulation. The findings reveal that curriculum collaboration is systematically organized through integrated planning, synchronized implementation between tahfidz schedules and formal learning, and periodic evaluation based on academic and tahfidz assessments. This integration demonstrably improves students’ fluency, accuracy, and consistency in Qur’an memorization. However, key challenges include limited time management, heterogeneous student motivation and ability, and adaptation to evolving national curriculum policies. The study highlights that integrated curriculum design offers an effective Islamic education model that strengthens both Qur’an memorization and academic achievement.